Quality of life of veterans of sports with osteochondrosis of the lumbosacral spine - Oleksiy Goncharov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to establish the effect of a comprehensive program of physical rehabilitation on the quality of life of wrestlers - veterans of sports with osteochondrosis of the lumbosacral spine in the training motor regime. Material & Methods: 34 athletes-veterans at the age of 36-45 years, a kind of struggle - judo and sambo-wrestling took part in the study. Sports qualification of athletes: MS - 25 people, MSIG - 9 people. The test was carried out on the verbal assessment scale of pain, the degree of vertebro-neurological disorders was assessed, the standard of living for the Oswestrovsky questionnaire was determined. Results: after application of the proposed comprehensive physical rehabilitation program for wrestlers - veterans of sports of the MG in 68% of cases, complaints were absent, the degree of vertebro-neurological disorders decreased, the results of the questionnaire on the Oswestrovsky questionnaire showed a statistically significant decrease in complaints of pain in various spheres of life. Conclusion: the positive influence of the developed program of physical rehabilitation on the quality of life of wrestlers - veterans of sports are proved.